Pregnancy in women with multiple sclerosis in France from 2010 to 2015: Incidence, outcomes, and exposure to disease-modifying therapies. (April 2022) - Tillaut, Hélène; Degrémont, Adeline; Kerbrat, Sandrine; Roux, Jonathan; Le Page, Emmanuelle; Mainguy, Christelle; Duros, Solène; Polard, Elisabeth; Leray, Emmanuelle
Background: Multiple sclerosis (MS) is usually diagnosed between 20-40 years old, when women often plan to have children. Objective: Our objectives were to estimate pregnancy incidence rates in women with multiple sclerosis (MS), and to describe the use of disease-modifying therapies (DMTs) before conception and during pregnancy, and pregnancy outcomes. Methods: This retrospective cohort study included all 15- to 49-year-old women with MS in the French national health insurance database over 2010–2015. A pregnancy was exposed if a DMT reimbursement claim occurred during pregnancy or in the 14 preceding days. We used zero-inflated negative binomial (ZINB) regression models to estimate incidence rates and ordinal and multinomial regression models to estimate DMT exposure and pregnancy outcomes. Results: The pregnancy incidence rate was 4.5 per 100 person-years. The probability of having a DMT-exposed pregnancy increased from 0.22 in 2010 to 0.30 in 2015. The probability of live birth was 0.72 (95% CI = 0.70–0.74) for exposed pregnancies (varied considerably among DMTs), 0.77 (95% CI = 0.76–0.79) without treatment, and 0.81 (95% CI = 0.79–0.83) if treatment was stopped within the previous year. Conclusion: In this population-based study, we showed an increase of exposed pregnancies over time, beta-interferon and glatiramer acetate being the most used DMTs and associated with the highest probabilities of live birth. Interrupted exposed pregnancies may reflect undesired pregnancies or fear of an adverse outcome, while recent DMT stop probably reflects pregnancy planning.